A STUDY ON A MEASUREMENT SYSTEM FOR DETERMINING BULK DENSITY OF UNSATURATED SOILS BASED ON SOIL GAS PERMEABILITY - Shang Gao; Xianliang Wang; Yi-Jia Wang; Wenqi Zhao; Weifan Zhou (Engenharia Agrícola)
ABSTRACT Soil compaction alters soil structure, reduces soil air permeability, and adversely impacts crop growth. However, the rapid field detection of soil compaction remains a significant technical challenge. To address this issue, this study describes the development of an unsaturated soil bulk density measurement system based on soil air permeability, which enables the estimation of soil compaction through the measurement of soil air permeability. The system uses a specially designed soil probe that injects air into the soil at a constant pressure (P0) and flow rate (Q0). The steady-state air pressure (ΔP0) and flow rate (ΔQ0) at a radius r0 were recorded to calculate the soil gas permeability coefficient (ka). Laboratory experiments demonstrated a significant relationship between the soil gas permeability coefficient (ka), soil bulk density (ρ), and soil moisture content (w): soil compaction, which increases the bulk density, markedly reduces ka, while a higher soil water content further diminishes air permeability. Using experimental data, a bulk density estimation model was constructed with ka and w as independent variables. Field validation showed that the model achieved an accuracy of R2=0.72, thus demonstrating its reliability. This method is operationally straightforward, and allows for the rapid assessment of soil compaction. It provides a robust tool for precision field management and enhanced crop productivity.